2014
DOI: 10.1016/j.pain.2013.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Sensory findings after stimulation of the thoracolumbar fascia with hypertonic saline suggest its contribution to low back pain

Abstract: Injection of hypertonic saline into deep tissues of the back (subcutis, muscle, or the surrounding fascia) can induce acute low back pain (LBP). So far, no study has analyzed differences in temporal, qualitative, and spatial pain characteristics originating from these tissues. The current study aimed to investigate the role of the thoracolumbar fascia as a potential source of LBP. In separate sessions, 12 healthy subjects received ultrasound-guided bolus injections of isotonic saline (0.9%) or hypertonic salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 67 publications
6
126
1
4
Order By: Relevance
“…In addition, each pain modality was rated with respect to the sensory and affective components after the respective block was completed. We used an extended German version of the Pain Sensation Questionnaire (Schmerz-Empfindungsskala, SES), 16,19,41 containing items describing affective or sensory pain components. It yielded sensory and affective pain scores derived from a list of 28 pain-related items each of which was rated on a 0 to 3 ordinal scale (0 5 does not apply, 1 5 applies somewhat, 2 5 applies mostly, 3 5 applies fully).…”
Section: Ratingsmentioning
confidence: 99%
“…In addition, each pain modality was rated with respect to the sensory and affective components after the respective block was completed. We used an extended German version of the Pain Sensation Questionnaire (Schmerz-Empfindungsskala, SES), 16,19,41 containing items describing affective or sensory pain components. It yielded sensory and affective pain scores derived from a list of 28 pain-related items each of which was rated on a 0 to 3 ordinal scale (0 5 does not apply, 1 5 applies somewhat, 2 5 applies mostly, 3 5 applies fully).…”
Section: Ratingsmentioning
confidence: 99%
“…The idea of fascial nociception is old and has led the way to a number of different treatments for neck pain. 1,7,10,11 This idea needs to be transferred to postoperative care. Anatomically, during a posterior cervical spine exposure, the surgeon must pass 2 different fascia layers while dissecting through the posterior cervical space: the trapezius muscle and the deep cervical fasciae, which lie over the deeper cervical muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Injections into tendon and tendon-bone junction sites were found to be more sensitive than injections into the muscle belly [38]. Sensitivity to pain was not found to be a strictly volume-driven process because ultrasound-guided injections of isotonic saline into fascia resulted in less pain than hypertonic saline injections even though both fluids distended the fascia [39]. The innervation profile of fascia may partially explain why these injections result in pain.…”
Section: Innervationmentioning
confidence: 94%
“…Studies have shown that intense local and referred pain occurs with injection of hypertonic saline into the tendons and fascia [38][39]. Injections into tendon and tendon-bone junction sites were found to be more sensitive than injections into the muscle belly [38].…”
Section: Innervationmentioning
confidence: 99%